PENGARUH KONSENTRASI LARUTAN GARAM DAN WAKTU - Kurniawan, Ronny (Jurnal Teknik Kimia, 2008)
Catfish is a kind of fish that has high protein rate around 20% mass that can be exploited onthe application knowledge of food biotechnology, and one of protein resources for Indonesia society.The application is as raw material soy sauce making.The experiment of soy sauce making that made of the catfish conducted by pulverizing thecatfish flesh then mixed it up with pulverized pineapple (containing bromelin enzyme) and water. Thecomparison mass is (g):mass (g):volume (ml) with the comparison value 1:2:1 and pH 6-7. All of thematerial has to be put the incubator as long as 3 days with the temperature 50o Keywords : soy sauce, fermentation, catfish, streptococcus lactis bactery, bromelinC. The hydrolysis result added with salt in the concentration 3% (mass/volume), 5% (mass/volume), 9%(mass/volume) and acidbactery lactit streptococcus lactis which further on separated it so it produced the fish soy saucefiltrate.The purpose of this research are to analyze the influence of salt condensation concentrationand the time of processed salt condensation fermentation by using 2 sided variant analysis method andto analyze totalize dissolve nitrogen content and organoleptic test including taste, color and scent toget soy sauce with quality. The result shows the highest protein rate is got on condensationconcentration variation of 3% and 7 day, hydrolysis time with protein rate of 17.95%. While accordingto organoleptic test the sauce which is produced accepted enough by society including taste, scent andcolor.